2008
DOI: 10.1172/jci35875
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling regulates epithelial-mesenchymal transition during biliary fibrosis in rodents and humans

Abstract: Epithelial-mesenchymal transitions (EMTs) play an important role in tissue construction during embryogenesis, and evidence suggests that this process may also help to remodel some adult tissues after injury. Activation of the hedgehog (Hh) signaling pathway regulates EMT during development. This pathway is also induced by chronic biliary injury, a condition in which EMT has been suggested to have a role. We evaluated the hypothesis that Hh signaling promotes EMT in adult bile ductular cells (cholangiocytes). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
366
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(384 citation statements)
references
References 89 publications
(132 reference statements)
15
366
2
1
Order By: Relevance
“…Upon activation by specific ligands, β-catenin is released from the membrane and promotes transcription of genes involved in mesenchymal phenotype induction [48]. Notch and Hedgehog, acting as morphogens, are also able to activate EMT by regulating the expression of Snail [49,50].…”
Section: The Epithelium To Mesenchymal Transitionmentioning
confidence: 99%
“…Upon activation by specific ligands, β-catenin is released from the membrane and promotes transcription of genes involved in mesenchymal phenotype induction [48]. Notch and Hedgehog, acting as morphogens, are also able to activate EMT by regulating the expression of Snail [49,50].…”
Section: The Epithelium To Mesenchymal Transitionmentioning
confidence: 99%
“…26 There is evidence that proliferating cholangiocytes have a role in the induction of fibrosis, either directly through epithelial-mesenchymal transition, 27 or indirectly through the activation of hepatic stellate cells. 28 In fact, targeting proliferating biliary epithelia might provide a novel antifibrotic therapy in the liver. 29 Several studies have shown that the induction of iNOS and NO synthesis are also implicated in the promotion of cell growth in cholangiocytes.…”
Section: Protein S-nitrosation During Cholestasismentioning
confidence: 99%
“…The acquisition of these enhanced properties by reactive cholangiocytes is consistent with our observation that Foxl1 is only expressed in conditions associated with cholangiocyte injury. Diehl and colleagues have recently reported that the sonic hedgehog pathway is reactivated in response to bile duct ligation in rodents [7][8][9] and that hedgehog ligands secreted by hepatic stellate cells enhance cholangiocyte viability and motility. 7 Foxl1 is a downstream target of the sonic hedgehog signaling pathway in the gut 6 and it is reasonable to speculate that Foxl1 may represent an important hedgehog target responsible for the effects of sonic hedgehog on cholangiocyte function during cholestatic liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Although nothing is known about the function of Foxl1 in the liver, in the gut, Foxl1 is downstream of the hedgehog pathway and is a mediator of the wnt/bcatenin pathway, two signaling pathways that have been linked to cholangiocyte viability and proliferation, respectively. [6][7][8][9][10][11] Taken together, these findings led us to investigate whether Foxl1 is important for cholangiocyte viability and/or proliferation following bile duct injury. Foxl1 À/À mice do not exhibit any baseline liver abnormalities indicating that Foxl1 is dispensable for liver development.…”
mentioning
confidence: 98%